Percolation threshold of carbon nanotubes filled unsaturated polyesters - Battisti, Andrea; Skordos, Alexandros A.; Partridge, Ivana K. (Elsevier Science B.V., Amsterdam., 2010)
This paper reports on the development of electrically conductive nanocomposites containing multi-walled carbon nanotubes in an unsaturated polyester matrix. The resistivity of the liquid suspension during processing is used to evaluate the quality of the filler dispersion, which is also studied using optical microscopy. The electrical properties of the cured composites are analysed by AC impedance spectroscopy and DC conductivity measurements. The conductivity of the cured nanocomposite follows a statistical percolation model, with percolation threshold at 0.026 wt.% loading of nanotubes. The results obtained show that unsaturated polyesters are a matrix suitable for the preparation of electrically conductive thermosetting nanocomposites at low nanotube concentrations. The effect of carbon nanotubes reaggregation on the electrical properties of the spatial structure generated is discussed.
Keywords: Carbon nanotubes; Nano composites; Polymers; Electrical properties; Unsaturated polyester resin